Aquatic Therapy Improves Outcomes for Subacute Stroke Patients by Enhancing Muscular Strength of Paretic Lower Limbs Without Increasing Spasticity: A Randomized Controlled Trial. (November 2016) - Zhang, Yue; Wang, Yi-Zhao; Huang, Li-Ping; Bai, Bei; Zhou, Shi; Yin, Miao-Miao; Zhao, Hua; Zhou, Xiao-Na; Wang, Hong-Tu
ABSTRACT: Purpose: The aim of this study was to evaluate the effects of an aquatic exercise program designed to enhance muscular strength in paretic lower limbs in subacute stroke patients. Method: Thirty-six subacute stroke patients were randomly divided to a conventional or an aquatic group ( n = 18 each). Outcome measures were assessed at baseline and after 8 wks of training. For the paretic lower limbs, maximum isometric voluntary contraction strength of the rectus femoris and biceps femoris caput longus and the tibialis anterior and lateral gastrocnemius was measured. Cocontraction ratios during knee extension and flexion and ankle dorsiflexion and plantarflexion were calculated respectively. In addition, Modified Ashworth Scale, Functional Ambulation Category, and Barthel Index were assessed. Results: Compared with the conventional intervention, the aquatic intervention resulted in significantly higher knee extension ( P = 0.002) and ankle plantarflexion torque ( P = 0.002), accompanied with a significantly lower knee extension cocontraction ratio in the paretic limb ( P = 0.000). Functional Ambulation Category ( P = 0.009) and Barthel Index ( P = 0.024) were greater in aquatic group than conventional group posttreatment. Modified Ashworth Scale scores did not show any differences between groups. Conclusions: Aquatic exercise enhanced muscle strength in paretic lower limbs and improved muscle cocontraction without increasing spasticity in subacute stroke patients. Abstract : Supplemental digital content is available in the text.